A Review of Researches on the Relationship Between Critical Thinking and Emotion at Home and Abroad - Li, Yingxin; Sun, Yaru (Pacific International Journal, 2024)
Critical thinking is a key component of essential literacy skills, and it plays a crucial role in students' learning and development. Research shows that emotions have a significant influence on individual thinking activities, and they are important non-intellectual factors in developing students' critical thinking. Up to now, research scholars at home and abroad have conducted a lot of empirical studies to explore the possible relationship between the two variables. However, there is still a lack of research to systematically provide a holistic view. The current study is trying to present a comprehensive network of critical thinking and emotions through the discussion on the four-aspect correlation, that is, the correlation between critical thinking and negative emotion, critical thinking and emotional intelligence, critical thinking, emotion and academic achievement, and critical thinking, emotion and psychological cognition. The study also puts forward the limitations of the current research from the perspectives of research methods, research objects, and research contents, as well as the prospect of future research.